Tren Penelitian dengan Teori Unified Theory of Acceptance and Use of Technology (UTAUT) dalam Jurnal Scopus Berdasarkan Analisis Bibliometrik - Sumpena, Agus; Pratiwi , Gita; Arum, Intan Nurul Tanjung; Farodiyah, Nanda Nurul; Apriliyanti, Natasya Ayu (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Scopus indexed journal publications are highly important in the academic world as they indicate high quality and credibility of research. Scopus is one of the largest and most reputable international databases for scientific publications, managed by Elsevier. Publishing in Scopus-indexed journals offers numerous significant benefits for researchers and academics. This study aims to identify and analyze research trends using the Unified Theory of Acceptance and Use of Technology (UTAUT) in Scopus-indexed journals. The method used is quantitative with bibliometric analysis, involving data collection from the Scopus database, citation network mapping, and keyword analysis. The results show a significant increase in the number of publications using UTAUT from 2019 to 2023. The study also identifies the most productive authors, institutions, and countries in this field. Additionally, keyword analysis reveals that topics such as consumer behavior patterns, education, and technology development are trending topics and main focuses in UTAUT research. These findings provide important insights for researchers and practitioners regarding the development and future direction of UTAUT research.